Sunflower: a potential fructan-bearing crop? - Martínez Noël, Giselle María Astrid (2015)
Grain filling in sunflower (Helianthus annuus L.) mainly depends on actual photosynthesis, being the contribution of stored reserves in stems (sucrose, hexoses, and starch) rather low. Drought periods during grain filling often reduce yield. Increasing the capacity of stem to store reserves could help to increase grain filling and yield stability in dry years. Fructans improve water uptake in soils at low water potential, and allow the storage of large amount of assimilates per unit tissue volume that can be readily remobilized to grains. Sunflower is a close relative to Jerusalem artichoke (H. tuberosus L.), which accumulates large amounts of fructan (inulin) in tubers and true stems. The reason why sunflower does not accumulate fructans is obscure. Through a bioinformatics analysis of a sunflower transcriptome database, we found sequences that are homologous to dicotyledon and monocotyledon fructan synthesis genes. A HPLC analysis of stem sugar composition revealed the presence of low amounts of 1-kestose, while a drastic enhancement of endogenous sucrose levels by capitulum removal did not promote 1-kestose accumulation. This suggests that the regulation of fructan synthesis in this species may differ from the currently best known model, mainly derived from research on Poaceae, where sucrose acts as both a signaling molecule and substrate, in the induction of fructan synthesis. Thus, sunflower might potentially constitute a fructanbearing species, which could result in an improvement of its performance as a grain crop. However, a large effort is needed to elucidate how this up to now unsuspected potential could be effectively expressed.